Eu estou com todos : Ayahuasca e o contínuo ilimitado - Bezerra, Miguel Firmeza (2018)
ABSTRACT The following study argues about Ayahuasca and the possibility of proper knowledge attributed to it. Ayahuasca is one of the many names attributed to a beverage of indigenous origin made of two plants from the Amazonian rainforest. There is, among the peoples which use this drink, the belief that it is bearer of a multiple and vast knowledge. Our study is guided by the observation and analysis of a process of self-experimentation with Ayahuasca allied to bibliographical research about the aforementioned issue and aims at exploring what the nature of such knowledge is. Through a dive in the experienced processes throughout the research period, we extracted some results to this question, reaching the consideration that, other than discontinuous, fragmentary, formal and dimensional nature predominant in the Occidental perception of the real, the knowledge derived from Ayahuasca makes us take part in a continuous, limitless and non-dimensional aspect of reality.